Proses Belajar Masyarakat secara Informal dalam Pengembangan Usaha Jasa Sepeda Onthel - Rozi, Muhammad Fahrur; Wahyuni, Sri; Sopingi, Sopingi (Journal of Nonformal Education and Community Empowerment, 2018)
This inspires the researcher to implement research. The aim of the research is to describe the informal learning process of the society to develop their â€œonthelâ€ rental businesses. This research employed a qualitative research design using a case study approach. The research setting was in Tulungrejo village, Pare, Kediri. Informants of the research were the owners of â€œonthelâ€ rental business namely Mr. No and HF as well as the director of Mahesa Institute. The data collection techniques consisted of depth interview, observation, and documentation. The technique of data analysis was conducted in several stages including data process, data description, data classification, data interpretation, data presentation, and conclusion draw. The testing process of validity on findings was implemented using triangulation of sources and techniques. The results showed that the development of bicycle rental business is actualized in the informal community learning process.